2018
DOI: 10.1149/2.0171809jss
|View full text |Cite
|
Sign up to set email alerts
|

Water Outlet Design of Wet Cleaning Bath for 300-mm Diameter Silicon Wafers

Abstract: Water motions influenced by an outlet of a batch-type 300-mm diameter silicon wafer wet cleaning bath were experimentally and numerically studied in order to quickly remove the contaminants from the bath. The outlet consisting of a pinhole arrays (PA) near the top edge of the bath side wall was designed and evaluated along with an ordinary overflow (OF) outlet. The experiment showed that the amount of a blue-colored ink, used as a tracer, in the bath having both the OF-and the PA-outlets decreased faster than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…The water flow rate was mainly 17 l min −1 , similar to the previous studies. [12][13][14] For studying the appropriate water flow rate, rates between 5 and 30 l min −1 were evaluated. A blue-colored ink was used as a tracer for visualizing the water motion, which was captured using a video camera from the front and right sides.…”
Section: Experimental Procedures and Numerical Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The water flow rate was mainly 17 l min −1 , similar to the previous studies. [12][13][14] For studying the appropriate water flow rate, rates between 5 and 30 l min −1 were evaluated. A blue-colored ink was used as a tracer for visualizing the water motion, which was captured using a video camera from the front and right sides.…”
Section: Experimental Procedures and Numerical Calculationsmentioning
confidence: 99%
“…The previous studies [7][8][9][10][11][12][13] showed that the water recirculation, a kind of stable vortex, could be managed by means of a simple measure, such as employing pinholes near the top of the bath wall as a water outlet. When the nearest neighbor pinholes were within 1.5 cm or less, they could behave and work as an integrated wide water outlet.…”
mentioning
confidence: 99%